Perilaku Komunikasi Hiperpersonal Pasangan Muslim pada Online Cinta - Pambayun, Ellys Lestari (El Madani: Jurnal Dakwah dan Komunikasi Islam, 2020)
The study of hyperpersonal communication behavior of Muslim couples through online love comes from observing the phenomenon of the activities of internet users of different sexes who interact socially, intensely, romance, even intimate even though they are not married. Despite the prohibition of Islamic religion about dating, problems have been found, that chat rooms on Facebook and Whastapp have indicated that love relationships are easier and more open than real life, often without barriers or religious norms, social status, education, physical differences, state , marital status, and age. In addition, online love has made it easy for people to find a partner (jodo), whether religious or not, can be used as an affair media for couples whose marital life is in disarray, and a media for disloyal acts to their partners. The approach used is Social Hermeneutics, Hyperpersonal Communication theory and the concept of Islamic relations. The methodology used by the communication mediated computer (CMC) method through online interviews of online couples in love in various characteristics and patterns of interaction or communication The results of the study suggest that in hyper-personal communication, Muslim couples through cyberlovers on Facebook and Watsapp construct self-presentation, self-attribution, and communication intensification. to his partner. These Muslim couples can play a role as selective senders, but they lack control over non-religious communication. As recipients, couples are less able to be balancing and adjusting their communication. In the channel, the pairs communicate asynchronously and synchronously where the informants send each other "intensive messages" or continuously without space and time. However, the nature of this online couple's relationship is not in accordance with the ta'aruf, khitbah and ghasiyah nau frame contained in Islamic values.